Implementasi Model Make A Match untuk Meningkatkan Hasil Belajar Matematika Siswa SD - Veronica Yonita Wongkar; Deiby Tiwow (Departement of Mathematics Education, 2022)
The purpose of this study is to apply the Make a Match learning model to fifth-grade students at SD Catholic 07 Xaverius Manado in order to improve mathematics learning outcomes. Classroom Action Research (PTK) is a type of research that is carried out in two cycles. 32 students from class V SD Catholic 07 Xaverius Manado participated in this study. Tests, observation, and documentation were used to gather data. Then, both quantitative and qualitative analyses of the collected data were performed. According to the findings, the average value of student activity in the first cycle was 75, and it increased to 87 in the second cycle. In the first cycle, the average teacher activity was 75, and in the second cycle, it increased to 88.92. In the first test, the percentage of student learning outcomes was 44.12%, in the first cycle, it was 74.68%, and in the second cycle, it was 92.66%. The Make a Match learning model has the potential to improve student math learning outcomes, it can be concluded.